Manipulating and quantifying spin states in solution as a function of pressure and temperature. Issue 2 (8th December 2017) - Hogue, Ross W.; Lepper, Christopher P.; Jameson, Geoffrey B.; Brooker, Sally
Abstract : This new 'single compartment tube' 1 H NMR methodology for determining spin states under high pressures (up to 240 MPa) has implications for the study of magnetic, catalytic and biochemical processes. Abstract : Monitoring the spin states of species in solution is a crucial aspect of understanding magnetic properties as well as spin-labile sensing, supramolecular, catalytic and biochemical processes. Herein, we describe the first quantitative variable-pressure and variable-temperature method of determining spin states in solution, demonstrate that it is accurate, and identify a simultaneous T and P sensor system.